PENGARUH KOMITE AUDIT DAN RISIKO BAWAAN AUDIT TERHADAP FEE AUDIT (Studi Terhadap Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Fauzan, Akram; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2024)
The aims from this study is investigate the relationship between audit committee and inherent audit risk on audit fees. The independent variables used in this research is audit committee size, frequency of audit committee meetings, audit committee expertise, profitability, liquidity and solvency. Then the dependent variable in this research is audit fees.The population used in this study consists of companies in manufacturing sector listed on the Indonesian Stock Exchange. Using purposive sampling method, 270 samples used from companies in manufacturing sector which published annual reports for the period 2019-2021. This study uses multiple regression analysis to examine audit fees, audit committee size, frequency of audit committee meetings, audit committee expertise, profitability, liquidity and solvency.The result from this study show that audit committee expertise has a significant negative influence on audit fees. As for the size of the audit committee, frequency of audit committee meetings, profitability, liquidity and solvency do not significantly influence audit fees.